Computer Performance Evaluation and Benchmarking SPEC Benchmark Workshop 2009, Austin, TX, USA, January 25, 2009, Proceedings - Kaeli, David (Programming and Software Engineering, 2009)
This book constitutes the proceedings of the SPEC Benchmark Workshop 2009 held in Austin, Texas, USA on January 25th, 2009. The 9 papers presented were carefully selected and reviewed for inclusion in the book. The result is a collection of high-quality papers discussing current issues in the area of benchmarking research and technology. The topics covered are: benchmark suites, CPU benchmarking, power/thermal benchmarking, and modeling and sampling techniques.